Precarious balance : Sinhala Buddhism and the forces of pluralism - Smith, Bardwell L., 1925-2022 (Studies in Religion and Culture., 2022)
"This book explores the history of Buddhism in Sri Lanka from one of its earliest kings to its present-day conflicts"--